Toxicity Assessment of Biogenic Gold Nanoparticles on Crop Seeds and Zebrafish Embryos: Implications for Agricultural and Aquatic Ecosystems - Botteon, Caroline E. A.; Pereira, Anderson do E. S. [UNESP]; de Castro, Larissa P.; Justino, Isabela A.; Fraceto, Leonardo F. [UNESP]; Bastos, Jairo K.; Marcato, Priscyla D. (American Chemical Society (ACS), 2025)
The demand for food production has been growing exponentially due to the increase in the global population. Innovative approaches to enhance agricultural productivity have been explored, including the new applications of nanoparticles in agriculture. The nanoparticle application in agriculture can generate environmental and human health risks since nanoparticles can contaminate the soil and inevitably reach groundwater, potentially causing toxicity in aquatic organisms. In this study, we evaluated the benefits and toxicity of gold nanoparticles (GNPs), synthesized via green chemistry, on the growth of cultivated plants and in the zebrafish embryo model. GNPs were synthesized through an economical and environmentally friendly method using Brazilian red propolis (BRP) extract (BRP-GNPs). BRP-GNPs exhibited negative and positive effects on plant germination, depending on the concentration tested and the plant species involved. Moreover, BRP-GNPs induced developmental toxicity in fish embryos in a dose-dependent manner. Our results provide valuable insights for assessing the environmental risks of biogenic GNPs.